Stories for Asylum: Narrative and Credibility in the United States’ Political Asylum Application - Holland, Madeline (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2018)
This article examines the narrative demands placed on asylum seekers to the United States. Engaging with scholars from the felds of narratology and literature, this article argues that “telling a story” is an implicit requirement of the asylum application process to the United States, and that the stories of asylum seekers are evaluated for their truthfulness on the basis of criteria that align with literary standards of veracity. The article examines the implications of bringing these literary standards of veracity to bear on asylum seekers’ stories, and explores the ways in which a “true” story told by an asylum seeker may fail to be recognized as such.